Treatment of Periodontitis for the Prevention of Endothelial Dysfunction: A Narrative Review - Parenti, Astrid; Paccosi, Sara; Cairo, Francesco; Defraia, Efisio (Current Vascular Pharmacology, 2015)
Endothelial dysfunction (ED) is the initial step in the development of atherosclerosis, leading to cardiovascular disease (CVD). It has been suggested that periodontal disease (PD) could be associated to pathogenesis of atherosclerosis, since it is able to trigger a host response with systemic inflammation. Although a number of epidemiological studies have shown that periodontitis could be associated with ED, it is still unclear whether periodontal treatment could improve ED and therefore cardiovascular outcomes. In this narrative review we analysed the literature in the databases of Medline under ‘‘endothelial function OR dysfunction OR vasodilatation’’, AND ‘‘periodontal disease” OR periodontal treatment” AND “cardiovascular disease” OR atherosclerosis AND “endothelial biomarker”. Research articles, systematic reviews and clinical trials were screened. ED could be related to periodontitis as well as to CVD. Periodontal treatment reduces the risk of teeth loss and may improve ED and the risk of CVD. Since controversial results exist, there is an urgent need for well-designed clinical trials to find and validate novel biomarkers of endothelial function, such as circulating endothelial progenitors, which may be crucial for further investigation of the association of PD with endothelial function and CVD.
Keywords: Endothelial dysfunction